2004
DOI: 10.1038/sj.mp.4001560
|View full text |Cite
|
Sign up to set email alerts
|

Human cannabinoid receptor 1: 5′ exons, candidate regulatory regions, polymorphisms, haplotypes and association with polysubstance abuse

Abstract: A number of lines of evidence make the gene that encodes the G-protein-coupled CB1/Cnr1 receptor a strong candidate to harbor variants that might contribute to individual differences in human addiction vulnerability. The CB1/Cnr1 receptor is the major brain site at which cannabinoid marijuana constituents are psychoactive as well as the principal brain receptor for endogenous anandamide ligands. It is densely expressed in brain circuits likely to be important for both the reward and mnemonic processes importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
325
4
3

Year Published

2005
2005
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 235 publications
(350 citation statements)
references
References 49 publications
17
325
4
3
Order By: Relevance
“…Variability of these results could be explained by several confounding factors. Stratification bias could be the first of these factors because of the differences in allelic distribution among various ethnicities as it was recently demonstrated in a study by Zhang et al 16 In previous studies reviewed in Table 2, the most common allele types were the (AAT)15 and (AAT)16 in Chinese 17 and Japanese 19 controls, and the (AAT)13, (AAT)15 and (AAT)17 in French-Caucasian controls; 6 between African-American controls 16 and the AfricanCaribbean controls in the present study inconsistent results were found.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Variability of these results could be explained by several confounding factors. Stratification bias could be the first of these factors because of the differences in allelic distribution among various ethnicities as it was recently demonstrated in a study by Zhang et al 16 In previous studies reviewed in Table 2, the most common allele types were the (AAT)15 and (AAT)16 in Chinese 17 and Japanese 19 controls, and the (AAT)13, (AAT)15 and (AAT)17 in French-Caucasian controls; 6 between African-American controls 16 and the AfricanCaribbean controls in the present study inconsistent results were found.…”
Section: Discussionmentioning
confidence: 95%
“…One other study found a positive association in African-American polysubstance abusers, but the authors did not discuss this result. 16 Three other studies did not confirm the association. The first one 17 was performed with heroin dependents in a male and female Chinese population.…”
Section: Discussionmentioning
confidence: 96%
“…Using a case-control design, Comings et al (1997) reported an excess frequency of long (AAT) n repeats in a group of drug-dependent non-Hispanic Caucasians from Southern California (Comings et al 1997). Other groups have been unable to replicate this finding (Covault et al 2001;Heller et al 2001;Li et al 2000;Zhang et al 2004).…”
Section: Introductionmentioning
confidence: 92%
“…Single nucleotide polymorphisms (SNPs) adjacent to this site were reported to be associated with polysubstance abuse (Zhang et al 2004). We examined the association of 4 SNPs (rs6928499, rs806379, rs1535255, rs2023239) in the distal region of intron 2 of CNR1 both with individual substance dependence diagnoses (i.e., alcohol, cocaine, and opioids), as well as with polysubstance dependence.…”
Section: Introductionmentioning
confidence: 99%
“…18 CNR1 polymorphisms were found to be associated with polysubstance abuse, including alcoholism. 19 Thus, cannabinoids, which are the main component of marijuana, act with exocannabinoids on the endocannabinoid system, which plays a significant role in vulnerability to development of addiction and other mental disturbances. 20 CNR2 may also be associated with addiction vulnerability as a modulator of the reward system.…”
Section: Introductionmentioning
confidence: 99%